Towards a Multimodal Account of Post-Positioned Question Tags in Jordanian Arabic Conversation - Al-qaoud, Juman (Social Interaction. Video-Based Studies of Human Sociality, 2026)
This study explores the multimodal features of post-positioned question tags (PPQTs) and their temporal alignment, by using Conversation Analysis and interactional linguistics approaches. Data come from 20 hours of audio and video recordings of casual Jordanian Arabic conversations among 70 university students and graduates in Irbid City. By drawing on Jefferson (1981), Pomerantz (1984), and Stivers and Rossano (2010), the present microanalysis shows that PPQTs, such as sˤaħ? (‘right?’), together with specific nonverbal cues, pursue responses after an initial lack of uptake, while acknowledging their non-turn yielding functions.